Effects of Personal Values on Auditor’s Ethical Decisions: A Comparison of Pakistani and Turkish Professional Auditors - Karacaer, Semra (Journal of business ethics, 2009)
The aim of this study is to investigate the effects of personal values on auditor’s ethical decision-making in two countries, namely, Pakistan and Turkey. This study is the first that empirically addresses the role of values in the ethical decision-making processes of Pakistani and Turkish Professional auditors. This study surveys a random sample of these countries' professional certified auditors to assess their value preferences and reactions to an ethical dilemma. This study measures practicing auditors' value preferences by using the Rokeach value survey (RVS), and a case study is used to measure the reactions to an ethical dilemma involving client pressure for aggressive financial reporting. This study did not find statistically significant difference between the mean values of moral intensity in these two countries. On the other hand, we found statistically significant differences between the terminal and instrumental values of the auditors in the countries studied. This study suggests that perceptions of moral intensity influenced both ethical judgments and behavioral intensions.